Out-of-plane permeability measurement for reinforcement textiles: A benchmark exercise. (September 2021) - Yong, A.X.H.; Aktas, A.; May, D.; Endruweit, A.; Advani, S.; Hubert, P.; Abaimov, S.G.; Abliz, D.; Akhatov, I.; Ali, M.A.; Allen, T.; Berg, D.C.; et al.
Abstract: The out-of-plane permeability of two glass fibre fabrics was measured by 26 institutions using silicone oil as a test fluid. Participants in this study were free to select the test procedure, specimen dimensions and data analysis method, provided that testing was carried out at three target fibre volume fractions, 46%, 50% and 54%. While results showed a variability of two orders of magnitude between participants, most values were within a significantly narrower band. A majority of participants used 1D saturated test method. A few selected 1D unsaturated and 3D unsaturated flow method which gave very similar results. Focusing on analysis of data and results of 1D saturated flow measurements, results are not conclusive, but they are consistent with number of layers in a specimen, fibre volume fraction, injection pressure and sealing of specimen edges all having an effect on the measured permeability. Specifying limits for these parameters is expected to result in reduced scatter in measured permeability.